Functional impairment associated with increased severity of mental health disorders in Latin American chronic hemodialysis patients - Santacruz Juan; Santacruz Sahel; Coloma Ghery; Reinoso Paulo; Carlotta Sulbarán; Ana Vásquez; Paola Arévalo; Gabriela Santacruz; Nancy Mancheno; Cristóbal Santacruz (Archives of Renal Diseases and Management - Peertechz Publications, 2021)
Background: End-Stage Kidney Disease (ESKD) and associated complications are related with increased prevalence of psychological disorders. There is a growing trend of elderly and high comorbid individuals beginning chronic Hemodialysis Programs (HD) while there is limited knowledge about the influence of functional impairment and comorbidity burden in the prevalence of mental health disorders and life satisfaction on HD population. The purposes of this study were to report the local prevalence of psychological disorders, life satisfaction and self-reported health status as well to describe differences in functional status and comorbidity burden scores between patients with moderate/severe psychological disorders and those none/mild alterations of a Latin American chronic HD cohort. Methods: Transversal uni-center study in 139 Ecuadorian chronic and stable HD patients. Once patients were eligible to participate six tests were applied to explore functional status (Barthel Index and PPS score), depression, anxiety and stress prevalence (DASS-21 scale) comorbidity burden (Charlson Index), self-rated health state (EQ-5D/VAS) and satisfaction with life (SWLS score) Exclusion criteria were: Time in HD less than 6 months, recent hospitalization (less than 3 months) and severe cognitive impairment. Continuous symmetric variables were described as mean ± standard deviation or median and interquartile range if asymmetric. T-test was used for symmetric continuous variables, U-Mann-Whitney if asymmetric and chi-square for qualitative variables. Results: A total of 79 (55%) patients were male. Mean time in HD was 73 ± 47 months, with mean age 56 ± 15,7 years. Prevalence of moderate/severe mental health disorders were: depression (28%), anxiety (37%) and stress (34%). Moderate/severe depressed patients scored significatively lower in Barthel Index (p=0.048) and those with moderate/severe stress scored significatively lower in Barthel Index (p=0.025) and PPS score (p=0.030). Time in HD > 92 months was significatively related with moderate severe/anxiety (0.044). Unsatisfaction with life was found in 20% of patients and it was significatively related with lower functional Barthel Index (p=0.017) and PPS score (p=0.041) when compared with those satisfied with life. Patients with self-rated health status <70% on EQ-5D VAS scored significatively lower in Barthel Index (p=0.022) and PPS score (0.003) vs those with ≥70% score. No differences were found with age, CKD etiology, civil and laboral status.  Conclusions: Prevalence of mental health disorders is similar to other series reported. Patients with moderate/severe depression, stress, unsatisfaction with life, and low self-reported health state had worst functional status than those with none/mild alterations. Time in HD over 7.6 years was associated with higher intensity of anxiety.